IMPLEMENTASI PROGRAM PEMULIHAN EKONOMI NASIONAL PADA KANTOR PUSAT PT. BANK SULSELBAR - Mudjriah, Mudjriah; Fatmawati, Fatmawati; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the implementation of the National Economic Recovery program at the Head Office of PT. Bank Sulselbar using qualitative research methods, the number of informants is 10 people. The results of the research are 1) the program includes the realization of the distribution of PEN funds in phase I and phase II and the achievement of goals by implementing a program to increase the productive credit portfolio of the MSME segment. However, there were many obstacles that were passed, such as only new debtors, low purchasing power during the Covid-19 recovery, loan terms, declining economic growth, implementation of PSSB, business actors still observing economic growth conditions. 2) Implementing organizations consist of existing divisions designated in distribution and supported by complete facilities and infrastructure such as MSME Centers 3) Targets or parties to which PEN funds are provided consist of Services/Cooperatives, Industry, Infrastructure/Construction, Multi-Sector Productive , Financial/BPR and Other/Consumptive Intermediaries and how to act by making guidelines for the distribution of PEN funds Number SR/072/DRK/VIII/2021 and increasing the consumer credit portfolio, productive for the corporate and syndicated segments.